Endovascular treatment for acute basilar artery occlusion via persistent primitive hypoglossal artery: A case report. Issue 48 (3rd December 2021) - Park, Jung Soo; Shin, Byoung-Soo; Kang, Hyun Goo
Abstract: Introduction: Although their effectiveness and safety have not yet been established, endovascular treatments have recently been applied in the treatment of acute basilar artery occlusion. If not identified, persistent primitive hypoglossal artery, a rare variant of the posterior circulation, could be a barrier to the successful treatment of basilar artery occlusion. Patient concerns: An 83-year-old woman, who had been undergoing treatment for hypertension for 20 years, visited our hospital 3 hours after the onset of acute unresponsive mental deterioration. The patient was unresponsive to painful stimuli, and the pupils were equal and miotic. Diagnosis: Brain computed tomography angiography confirmed complete occlusion of the distal basilar artery and revealed a dilated branch arising from the right internal carotid artery at the C2 vertebral level. Interventions: Endovascular thrombectomy was performed directly via the right femoral artery. Complete recanalization was achieved via manual aspiration thrombectomy. Outcomes: Brain magnetic resonance imaging revealed multifocal cerebral infarctions in the bilateral thalamus, midbrain, and cerebellar vermis. The patient's neurological symptoms gradually improved. Conclusions: This is a rare case of basilar artery occlusion that was successfully treated with mechanical thrombectomy through persistent primitive hypoglossal artery. It is important to consider the potential clinical implications of this rare vascular variant.